Comprehensive and practical guidelines for reduction synthesis of atomically precise coinage–metal nanoclusters - Qinghua Xu; Xuekun Gong; Zixiao Zhao; Lin Wang; Jing Sun; Jinlu He; Simin Li; Hui Shen (Polyoxometalates, 2025)
As a model system for studying the structure–property relationship and surface coordination chemistry of metal nanomaterials, ligand-stabilized, atomically precise coinage–metal (Au, Ag, and Cu) nanoclusters (NCs) have attracted considerable attention. Extensive effort has been devoted to the synthesis and structural determination of metal NCs over the past decades, with the chemical reduction of high-valence metal ions in the presence of protective ligands laying the foundation. After examining over 200 synthetic examples of individual metal NCs prepared through direct reduction methods—using reactants such as single metals (Au, Ag, and Cu) or alloys (e.g., Au-Ag, Au-Pt), along with ligands such as phosphines, thiolates, and alkynyls, N-heterocyclic carbenes, halides, and their combinations, we propose comprehensive and practical guidelines for the reduction synthesis of ligand-stabilized metal NCs. This review aims to elucidate the potential introduction of robust synthetic prototypes for engineering these NCs, which have evolved from one-phase, two-phase, and miscible solution synthesis to solid-state synthesis. Several factors are crucial for optimizing synthesis, including the selection of precursors, reductant systems, and purification strategies. After presenting an expansive and critical perspective on this rapidly evolving field, we outline some promising future trends.